The impact of the COVID-19 Pandemic on Breastfeeding Practices among Mothers - Ayşe Ünsal; Tülay Kuzlu Ayyıldız (Çocuk Dergisi)
Objective: This study aimed to evaluate the impact of the COVID-19 pandemic on breastfeeding practices among mothers with infants aged 0– 24 months.Methods: The research was carried out at the Ankara City Hospital’s breastfeeding support/relactation clinic and mother-infant bonding service from December 2021 to May 2022. A sample of 511 mothers who visited these clinics during the study period, agreed to participate, and met the research criteria was included. Data collection was done using a descriptive data form.Results: The average age of the mothers was 28 ± 4.7 (18–44), and 51.66% had undergone cesarean delivery. Approximately 54.41% of the mothers were university graduates. During the pandemic, 13.0% of the mothers reported breastfeeding-related issues, and all those who faced problems refrained from seeking hospital assistance. Additionally, 12.14% of the mothers had COVID-19 during pregnancy, 76.13% contracted it after childbirth, and 69.70% of those who had COVID-19 discontinued breastfeeding. Furthermore, 28.79% of the mothers who continued breastfeeding reported feeling anxious while nursing. Approximately 57.6% of the mothers stated they did not receive any breastfeeding-related information during the pandemic, and 17.50% experienced breastfeeding issues after quarantine. While hospitalized due to COVID-19, 48.7% of the mothers breastfed their infants, 41.0% fed expressed breast milk and formula, and 10.3% exclusively used formula.Conclusions: The findings underscored the necessity for breastfeeding counseling services for mothers during the COVID-19 pandemic.